Mobile Ocean Bottom Seismometer Instrument (MOBSI) data from Arctic rivers, lakes, and seas ... - Angelopoulos, Michael; Ryberg, Trond; Rasmussen, Christian; Haberland, Christian; Juhls, Bennet; Dallimore, Scott; Boike, Julia; Overduin, Pier Paul (Zenodo, 2023)
We collected the data using the Mobile Ocean Bottom Seismic Instrument (MOBSI). The MOBSI is portable (9 kg) and consists of a water tight, heavy-duty pressure housing (diameter 30 cm, height 35 cm) containing a three-component, broad-band seismic sensor. There are three channels (two horizontal and one vertical) recorded by the built-in data logger to monitor ambient seismic noise. Deployed by a steel cable from a small boat or zodiac, the device was lowered to the bottom of the water bodies or top of the beach area (if present). The device recorded ambient seismic noise for a few minutes before being retrieved and moved to a new location. The steel cable was outfitted with a communications cable, which allowed for live data analysis and quality control via a shipboard monitor. This insured that the tilt of the instrument was correct (less than 5 degrees) and that the deployment time was sufficient. We stopped data collection until the "real-time" H/V ratio was stable, i.e., not changing with time. For all ...